2023
DOI: 10.1111/ctr.15180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution on postoperative outcomes following organ transplantation: Evidence from clinical investigations

Kittitorn Supphapipat,
Prangmalee Leurcharusmee,
Nipon Chattipakorn
et al.

Abstract: IntroductionAir pollution is a worldwide problem affecting human health via various body systems, resulting in numerous significant adverse events. Air pollutants, including particulate matter < or = 2.5 microns (PM2.5), particulate matter < or = 10 microns (PM10), ozone (O3), nitrogen dioxide (NO2), and traffic‐related air pollution (TRAP), have demonstrated the negative effects on human health (e.g., increased cerebrovascular, cardiovascular, and respiratory diseases, malignancy, and mortality). Organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 158 publications
0
0
0
Order By: Relevance
“…Further research has found that the failure of the emission reduction effect of haze pollution may lie in the failure of the technological innovation effect and population quality effect of low-carbon city construction, as well as regional heterogeneity. Supphapipat et al (2023) delved into the effects of air pollution on post-organ transplant outcomes, asserting that air pollution creates a hazardous environment affecting not only global human health but also post-transplant outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further research has found that the failure of the emission reduction effect of haze pollution may lie in the failure of the technological innovation effect and population quality effect of low-carbon city construction, as well as regional heterogeneity. Supphapipat et al (2023) delved into the effects of air pollution on post-organ transplant outcomes, asserting that air pollution creates a hazardous environment affecting not only global human health but also post-transplant outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%